Inside Back Cover: Ultrafast Independent N−H and N−C Bond Deformation Investigated with Resonant Inelastic X‐Ray Scattering (Angew. Chem. Int. Ed. 22/2017). Issue 22 (26th April 2017) - Eckert, Sebastian; Norell, Jesper; Miedema, Piter S.; Beye, Martin; Fondell, Mattis; Quevedo, Wilson; Kennedy, Brian; Hantschmann, Markus; Pietzsch, Annette; Van Kuiken, Benjamin E.; Ross, Matthew; Minitti, Michael P.; et al.
Abstract : Electronic and structural changes induced by photoexcitation of 2‐thiopyridone (2‐TP) were investigated with inelastic X‐ray scattering (RIXS). S. Eckert, J. Norell et al. describe in their Communication onpage 6088 ff. that an N site deprotonation RIXS signature of 2‐TP, established in synchrotron measurements, was identified on a femtosecond timescale using the free‐electron‐laser LCLS. Quantum chemical simulations ascribe the signature to N lone‐pair orbital formation and confirm that X‐ray induced dynamics are decoupled from the optically induced deprotonation.